Dynamic electric-field-induced magnetic effects in cobalt oxide thin films: towards magneto-ionic synapses. Issue 3 (5th January 2022) - Martins, Sofia; de Rojas, Julius; Tan, Zhengwei; Cialone, Matteo; Lopeandia, Aitor; Herrero-Martín, Javier; Costa-Krämer, José L.; Menéndez, Enric; Sort, Jordi
Abstract : ON–OFF ferromagnetism by magneto-ionics in cobalt oxide films is achieved in seconds by reducing the film thickness down to 5 nm. Cumulative effects are generated by voltage pulses at frequencies up to 100 Hz, being able to mimic synapse functions. Abstract : Voltage control of magnetism via electric-field-driven ion migration (magneto-ionics) has generated intense interest due to its potential to greatly reduce heat dissipation in a wide range of information technology devices, such as magnetic memories, spintronic systems or artificial neural networks. Among other effects, oxygen ion migration in transition-metal–oxide thin films can lead to the generation or full suppression of controlled amounts of ferromagnetism ('ON–OFF' magnetic transitions) in a non-volatile and fully reversible manner. However, oxygen magneto-ionic rates at room temperature are generally considered too slow for industrial applications. Here, we demonstrate that sub-second ON–OFF transitions in electrolyte-gated paramagnetic cobalt oxide films can be achieved by drastically reducing the film thickness from >200 nm down to 5 nm. Remarkably, cumulative magneto-ionic effects can be generated by applying voltage pulses at frequencies as high as 100 Hz. Neuromorphic-like dynamic effects occur at these frequencies, including potentiation (cumulative magnetization increase), depression ( i.e., partial recovery of magnetization with time), threshold activation, and spike time-dependent magnetic plasticity (learning and forgetting capabilities), mimicking many of the biological synapse functions. The systems under investigation show features that could be useful for the design of artificial neural networks whose magnetic properties would be governed with voltage.